The Korean Heart Rhythm Society's 2014 Statement on Antithrombotic Therapy for Patients with Nonvalvular Atrial Fibrillation: Korean Heart Rhythm Society - Jung, Byung Chun (Korean Circ J, 2015)
In patients with nonvalvular atrial fibrillation (AF), the risk of stroke varies considerably according to individual clinical status. The CHA(2)DS(2)-VASc score is better than the CHADS(2) score for identifying truly lower risk patients with AF. With the advent of novel oral anticoagulants (NOACs), the strategy for antithrombotic therapy has undergone significant changes due to its superior efficacy, safety and convenience compared with warfarin. Furthermore, new aspects of antithrombotic therapy and risk assessment of stroke have been revealed: the efficacy of stroke prevention with aspirin is weak, while the risk of major bleeding is not significantly different from that of oral anticoagulant (OAC) therapy, especially in the elderly. Reflecting these pivotal aspects, previous guidelines have been updated in recent years by overseas societies and associations. The Korean Heart Rhythm Society has summarized the new evidence and updated recommendations for stroke prevention of patients with nonvalvular AF. First of all, antithrombotic therapy must be considered carefully and incorporate the clinical characteristics and circumstances of each individual patient, especially with regards to balancing the benefits of stroke prevention with the risk of bleeding, recommending the CHA(2)DS(2)-VASc score rather than the CHADS(2) score for assessing the risk of stroke, and employing the HAS-BLED score to validate bleeding risk. In patients with truly low risk (lone AF, CHA(2)DS(2)-VASc score of 0), no antithrombotic therapy is recommended, whereas OAC therapy, including warfarin (international normalized ratio 2-3) or NOACs, is recommended for patients with a CHA(2)DS(2)-VASc score ≥2 unless contraindicated. In patients with a CHA(2)DS(2)-VASc score of 1, OAC therapy should be preferentially considered, but depending on bleeding risk or patient preferences, antiplatelet therapy or no therapy could be permitted.